Farmers Sued Over Deleted Climate Data. So the Government Will Put It Back. - Zraick, Karen (The New York Times, 2025)
The Agriculture Department pledged to restore online climate information that farmers said helped them do business, but which officials had deleted.
Keywords: Agriculture Department; Agriculture and Farming; Clayton, Walter J; Environmental Working Group; Global Warming; Greenhouse Gas Emissions; Natural Resources Defense Council; Northeast Organic Farming Assn; Suits and Litigation (Civil); United States Politics and Government